Control of Raised Intraocular Pressure after Intravitreal Triamcinolone Acetonide - A. Sami Memon, P. S. Mahar (Pakistan Journal of Ophthalmology, 2014)
Purpose: To determine the various treatment options including anti-glaucoma medication, laser and surgery to control the intraocular pressure (IOP) rise after Intravitreal triamcinolone acetonide (IVTA). Material and Methods: This prospective, interventional case series was carried out at Isra Postgraduate Institute of Ophthalmology, Karachi from May 2007 to April 2009. Patients with various choroidal and retinal vascular disorders, who were given IVTA in a dose of 4 mg / 0.1 ml and developed raised IOP ( > 21 mm Hg) were included in the study and followed up for one year. Results: Two hundred thirty seven eyes of 180 patients received IVTA during the study period. The mean age of patients was 50.86 ± 10.62 years with gender distribution of 99 male and 81 female. One hundred seventeen (49.36%) out of 237 eyes showed raised IOP after IVTA. Fifty two (21.94%) eyes showed an IOP between 25-30 mmHg while 65 (27.42%) had IOP of > 30 mm Hg. Successful control of IOP was defined as an IOP of less than 21 mm Hg. Thirty-four (29.05%) eyes were controlled with single beta-blocker therapy (Timolol maleate 0.5%) and 69 (58.97%) eyes were brought into control with combination therapy (Timolol maleate 0.5% + Dorzolamide 2%). Additional 4 (3.41%) eyes required Prostaglandin analogue (Latanoprost 0.005%) along with combination therapy for IOP control. Another 4 (3.41%) eyes were controlled with Argon laser trabeculoplasty and full medical treatment and remaining 6 (5.12%) eyes settled down with trabeculectomy with adjunctive mitomycin-C. Conclusion: Although IVTA is a cost-effective therapeutic agent against various choroidal and retinal disorders, 50% of the patients developed raised IOP > 21 mm Hg. Half of these patients required multiple drugs and almost 5% needed surgical intervention to control IOP under 21 mm Hg. Key words: Triamcinolone acetonide, Intraocular pressure, Glaucoma.